2005
DOI: 10.1111/j.0022-1112.2005.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Spawning aggregations of Lutjanus cyanopterus(Cuvier) on the Belize Barrier Reef over a 6 year period

Abstract: Cubera snapper Lutjanus cyanopterus aggregated to spawn at Gladden Spit, a salient sub‐surface reef promontory seaward of the emergent reef and near the continental shelf edge of Belize. Their spawning aggregations typically formed 2 days before to 12 days after full moon from March to September 1998–2003 within a 45 000 m2 reef area. Peak abundance of 4000 to 10 000 individuals was observed between April and July each year, while actual spawning was most frequently observed in May. Spawning was observed consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 21 publications
3
60
1
3
Order By: Relevance
“…They noted that spawning peaked from late September to November (boreal autumn) when temperatures were falling and rainfall was highest, although they also suggest that some spawning may occur in late March and April (boreal spring) when temperatures are higher (Doi & Singhagraiwan 1993). Heyman et al (2005) found that L. cyanopterus consistently formed spawning aggregations in relation to location, photoperiod, water temperature, and lunar cycle and that spawning was cued by time of day but not tides. Although no evidence of spawning aggregations was found during the current study, the reproductive status of the large schools of L. argentimaculatus recently being targeted by commercial fish trawls (Jason Stapley, Queensland Department of Primary Industries and Fisheries pers.…”
Section: Apodus L Griseus Sphyraena Barracuda Andmentioning
confidence: 92%
See 2 more Smart Citations
“…They noted that spawning peaked from late September to November (boreal autumn) when temperatures were falling and rainfall was highest, although they also suggest that some spawning may occur in late March and April (boreal spring) when temperatures are higher (Doi & Singhagraiwan 1993). Heyman et al (2005) found that L. cyanopterus consistently formed spawning aggregations in relation to location, photoperiod, water temperature, and lunar cycle and that spawning was cued by time of day but not tides. Although no evidence of spawning aggregations was found during the current study, the reproductive status of the large schools of L. argentimaculatus recently being targeted by commercial fish trawls (Jason Stapley, Queensland Department of Primary Industries and Fisheries pers.…”
Section: Apodus L Griseus Sphyraena Barracuda Andmentioning
confidence: 92%
“…In a review of the literature on the reproductive biology of lutjanids, grimes (1987) noted six species that spawned at or near the full moon and another that spawned around the full and new moons. Heyman et al (2005) found that L. cyanopterus generally spawned 3-8 days after the full moon and Davis & West (1993) observed a semilunar pattern of spawning activity for L. vittus, with peaks in the proportion of spawning females c. 3 days after the new moon and c. 6 days after the full moon. Spawning of lutjanids is not always lunarrelated and Jackson et al (2006) found no evidence of a lunar spawning cycle for L. campechanus in the gulf of Mexico.…”
Section: Apodus L Griseus Sphyraena Barracuda Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, larvae may remain in thin layers of food (Lasker, 1975) and reduce their diffusion owing to vertical differences in flow (shear diffusion (Warner, 1988). Similarly, several fish species spawn in circular motions that may create hydrodynamic vortexes (Okubo, 1988;Heyman et al, 2005). The influence of these small-scale events on larval dispersal over periods of weeks is unknown.…”
Section: Breaking the Behavioral Black Boxmentioning
confidence: 99%
“…Occurring in tropical and subtropical areas of all oceans, they constitute an important fishery resource worldwide (Allen, 1985;Heyman et al, 2005). The snappers are long-lived species, with medium to large size, inhabiting mainly shallow waters up to 450 m in depth, and feeding basically on crustaceans and mollusks (Nelson, 1984;Newman et al, 1996;Claro and Lindeman 2004).…”
Section: Introductionmentioning
confidence: 99%